The optimization of LNG dehydration process: article / Muhammad Hazim Mohd Shafie and Effah Yahya - Mohd Shafie, Muhammad Hazim; Yahya, Effah (2018)
Natural gas is one of the most important energy in this era. It being delivered to the consumers via pipelines by compressing the gas or liquefying the gas which is known as liquefied natural gas (LNG). Due to the technical and economic reasons, LNG is more favorable process to transport gas. Raw natural gas typically contains water vapour since it is found deep in underground reservoirs at high temperature and pressure. This research is done to simulate a gas dehydration process and to optimize the parameters in absorption dehydration process. The investigate parameters are the type of glycol used, the flow rate of the glycol, number of stages in absorber column, temperature of the reboiler and gas inlet temperature on glycol dehydration unit. The simulator used for this research was Aspen HYSYS. Based on the simulated data, an optimized parameters of dehydration process has been proposed. Results showed that triethylene glycol (TEG) is the most effective type of glycol followed by diethylene glycol (DEG) and ethylene glycol (EG). The higher the number of trays, the lower the amount of water content in the dry gas. The lower water content in the dry gas stream can be achieved by decreasing the temperature of the inlet gas of the absorption column. Results also shown that the higher the temperature of the reboiler the lower the water content of the natural gas stream. The optimum condition of gas dehydration was at 12 number of stages with 200°C reboiler temperature and 20°C inlet gas temperature.